Dynamic internal light shelf for tropical daylighting in high-rise office buildings - Lim, Yaik Wah (Elsevier Ltd, 2016)
Many high-rise offices in tropical regions do not have good quality of daylighting despite having abundance of daylight. Due to large glazed façade without external shading device, the office spaces receive high indoor illuminance with non-uniform distribution and glare problems. Thereby, efforts are needed to look into effective internal shading which is flexible to be installed by office tenants without modifying external façade. Daylighting performance of various internal light shelves was studied using Radiance-based simulation. The simulation results were validated against physical scaled model experiment and the results indicated significant Pearson correlations which ranged from 0.826 to 0.985. This study proved that high-rise office without any shading had poor daylighting quality with average illuminance as high as 11,193 lux and uniformity ratio below 0.1. Light Shelf (LS) 6 and LS 4 exhibited the best performance under intermediate sky, whereas LS 2 was the best under overcast sky. Although there was a decrease in illuminance level when comparing the optimum cases to the Base Case (ranging from −62.0% to −34.1%), the optimum cases showed a significant increase in distribution uniformity which was up to 178.6%. The finding has proposed a dynamic internal light shelf which could provide optimum daylighting performance for different sky conditions, times, months and orientations under tropical sky. Nevertheless, the proposed light shelf did not give significant improvement in Guth Visual Comfort Probability and CIE Glare Index. Thus, further studies are needed to consider the impacts of other types of shading and glazing on glare prevention.